Identification of Epithelial Phospholipase A2 Receptor 1 as a Potential Target in Asthma - Nolin, J.; Ogden, H.; Lai, Y.; Altemeier, W.; Frevert, C.; Bollinger, J.; Naika, G.; Kicic, Anthony; Stick, S.; Lambeau, G.; Henderson, W.; Gelb, M.; et al. (American Lung Association, 2016)
Secreted phospholipase A 2 s (sPLA 2 s) regulate eicosanoid formation and have been implicated in asthma. Although sPLA 2 s function as enzymes, some of the sPLA 2 s bind with high affinity to a C-type lectin receptor, called PLA 2 R1, which has functions in both cellular signaling and clearance of sPLA 2 s. We sought to examine the expression of PLA 2 R1 in the airway epithelium of human subjects with asthma and the function of the murine Pla2r1 gene in a model of asthma. Expression of PLA 2 R1 in epithelial brushings was assessed in two distinct cohorts of children with asthma by microarray and quantitative PCR, and immunostain ing for PLA 2 R1 was conducted on endobronchial tissue and epithelial brushings from adults with asthma. C57BL/129 mice deficient in Pla2r1 (Pla2r1 -/- ) were characterized in an ovalbumin (OVA) model of allergic asthma. PLA 2 R1 was differentially overexpressed in epithelial brushings of children with atopic asthma in both cohorts. Immunostaining for PLA 2 R1 in endobronchial tissue localized to submucosal glandular epithelium and columnar epithelial cells. After OVA sensitization and challenge, Pla2r1 -/- mice had increased airway hyperresponsiveness, as well as an increase in cellular trafficking of eosinophils to the peribronchial space and bronchoalveolar lavage fluid, and an increase in airway permeability. In addition, Pla2r1 -/- mice had more dendritic cells in the lung, higher levels of OVAspecific IgG, and increased production of both type-1 and type-2 cytokines by lung leukocytes. PLA 2 R1 is increased in the airway epithelium in asthma, and serves as a regulator of airway hyperresponsiveness, airway permeability, antigen sensitization, and airway inflammation.